The Effects of Ten Weeks of Lower-Body Unstable Surface Training on Markers of Athletic Performance - Cressey, Eric M.; West, Chris A.; Tiberio, David P.; Kraemer, William J.; Maresh, Carl M. (Journal of strength and conditioning research, 2007)
Initially reserved for rehabilitation programs, unstable surface training (UST) has recently grown in popularity in strength and conditioning and general exercise scenarios. Nonetheless, no studies to date have examined the effects of UST on performance in healthy, trained individuals. The purpose of this study was to determine the effects of 10 weeks of lower-body UST on performance in elite athletes. Nineteen healthy, trained members (ages 18-23 years) of a National Collegiate Athletic Association Division I collegiate men's soccer team participated. The experimental (US) group (n = 10) supplemented their normal conditioning program with lower-body exercises on inflatable rubber discs; the control (ST) group (n = 9) performed the same exercises on stable surfaces. Bounce drop jump (BDJ) and countermovement jump (CMJ) heights, 40- and 10-yard sprint times, and T-test (agility) times were assessed before and after the intervention. The ST group improved significantly on predicted power output on both the BDJ (3.2%) and CMJ (2.4%); no significant changes were noted in the US group. Both groups improved significantly on the 40- (US = -1.8%, ST = -3.9%) and 10-yard sprint times (US = -4.0%, ST = -7.6%). The ST group improved significantly more than the US group in 40-yard sprint time; a trend toward greater improvement in the ST group was apparent on the 10-yard sprint time. Both groups improved significantly (US = 2.9%, ST = -4.4%) on T-test performance; no statistically significant changes were apparent between the groups. These results indicate that UST using inflatable rubber discs attenuates performance improvements in healthy, trained athletes. Such implements have proved valuable in rehabilitation, but caution should be exercised when applying UST to athletic performance and general exercise scenarios.Initially reserved for rehabilitation programs, unstable surface training (UST) has recently grown in popularity in strength and conditioning and general exercise scenarios. Nonetheless, no studies to date have examined the effects of UST on performance in healthy, trained individuals. The purpose of this study was to determine the effects of 10 weeks of lower-body UST on performance in elite athletes. Nineteen healthy, trained members (ages 18-23 years) of a National Collegiate Athletic Association Division I collegiate men's soccer team participated. The experimental (US) group (n = 10) supplemented their normal conditioning program with lower-body exercises on inflatable rubber discs; the control (ST) group (n = 9) performed the same exercises on stable surfaces. Bounce drop jump (BDJ) and countermovement jump (CMJ) heights, 40- and 10-yard sprint times, and T-test (agility) times were assessed before and after the intervention. The ST group improved significantly on predicted power output on both the BDJ (3.2%) and CMJ (2.4%); no significant changes were noted in the US group. Both groups improved significantly on the 40- (US = -1.8%, ST = -3.9%) and 10-yard sprint times (US = -4.0%, ST = -7.6%). The ST group improved significantly more than the US group in 40-yard sprint time; a trend toward greater improvement in the ST group was apparent on the 10-yard sprint time. Both groups improved significantly (US = 2.9%, ST = -4.4%) on T-test performance; no statistically significant changes were apparent between the groups. These results indicate that UST using inflatable rubber discs attenuates performance improvements in healthy, trained athletes. Such implements have proved valuable in rehabilitation, but caution should be exercised when applying UST to athletic performance and general exercise scenarios.